Where hearing starts: the development of the mammalian cochlea. Issue 2 (5th June 2015) - Basch, Martin L.; Brown, Rogers M.; Jen, Hsin‐I; Groves, Andrew K.
Abstract: The mammalian cochlea is a remarkable sensory organ, capable of perceiving sound over a range of 10 12 in pressure, and discriminating both infrasonic and ultrasonic frequencies in different species. The sensory hair cells of the mammalian cochlea are exquisitely sensitive, responding to atomic‐level deflections at speeds on the order of tens of microseconds. The number and placement of hair cells are precisely determined during inner ear development, and a large number of developmental processes sculpt the shape, size and morphology of these cells along the length of the cochlear duct to make them optimally responsive to different sound frequencies. In this review, we briefly discuss the evolutionary origins of the mammalian cochlea, and then describe the successive developmental processes that lead to its induction, cell cycle exit, cellular patterning and the establishment of topologically distinct frequency responses along its length.